Physicochemical and biological characterization of the lipid particles with bovine serum albumin corona - Chen, Canfeng; Alfredo, Ying Ye; Lee, Yee Ying; Tan, Chin Ping; Wang, Yong; Qiu, Chaoying (Elsevier, 2024)
Diacylglycerol–based nanoparticles are promising bioactive delivery systems. However, limited understanding of their interaction with biological entities restricts their clinical use. This study investigated the protein corona formed on medium and long chain diacylglycerol (MLCD)-based solid lipid nanoparticles (NPs) modified by Polyoxethylene stearate (PEG) and compared to glyceryl tristearate (TG) and cetyl palmitate (CP) nanoparticles. Bovine serum albumin (BSA) formed corona with MLCD NPs through hydrophobic interactions and hydrogen bonding, contributing to a decrease in α–helix, an increase in β–sheet and a change in the microenvironment of Tyr residues. Owing to higher lipid hydrophilicity, MLCD NPs showed a much lower affinity for BSA than TG and CP NPs, and the binding constant with BSA was increased for larger NPs. PEG modification and the protein corona reduced the uptake of NPs by macrophages but exerted little influence on B16 cell. Among the NPs with different lipid core, the MLCD NPs showed a lower macrophages cell uptake but higher B16 cell uptake, suggesting a longer circulation time in blood but higher cancer cell internalization. This work shed light on the interactions between MLCD NPs and proteins, which is significant for application as nanocarriers with improved biological efficacy.